Patronage and Power: The Vicereines at the Court of Naples in the Reign of Philip III of Spain - Franganillo Álvarez, Alejandra (Renaissance and Reformation / Renaissance et Réforme, 2020)
Recently, several studies have focused on the figure of the viceroy in the Spanish Monarchy, especially in the Kingdom of Naples. However, far less attention has been paid to the role of the vicereines of Naples. The goal of my study is to investigate and clarify the significant roles held by these noblewomen at one of the most important viceregal courts of the Spanish Monarchy. I will focus on one vicereine in particular, Catalina de Zúñiga y Sandoval, 6th Countess of Lemos and sister to the Duke of Lerma (1599–1601), who developed an extensive political network through copious correspondences, requesting and distributing mercedes (dignities and favours) among family members and her clientage. A revisionary analysis of the vicereines’ roles at the Neapolitan court demonstrates how knowledge of their political contribution is essential for a deeper understanding of the economic and political strategies deployed by their families.